Analysis of the Social, Economic, and Ecological Impact of Mining Activities of PT. Gag Nickel on Society and Coral Reef Ecosystem in Gag Island, Raja Ampat District - Ulat, Muhamad Ali; Handayani, Handayani; Mulya, Anjar; Poltak, Hendra; Ismail, Ismail (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study analyses the social, economic, and ecological impact of PT. Gag Nickel mining activities on the society and coral reef ecosystem in Gag Island, Raja Ampat district. The data was obtained through in-depth interviews, observations, and questionnaires distributed to employees of PT. Gag Nikel and the surrounding community. The results of the research show that the presence of P.T. Gag Nikel has improved the income and well-being of the local population, with the majority of the population working as employees of the company. However, mining activities also cause damage to coral reef ecosystems, including soil erosion, sedimentation, and marine water pollution. In conclusion, in order to better sustainability, increased commitment of companies in managing environmental impacts and public involvement in decision-making related to mining activities is required. This research provides important insights for mining companies and other stakeholders in managing the impact of mining activities sustainably.